A Model of The Dynamic of The Relationship Between Exchange Rate and Indonesia's Export - Adam, Pasrun; Rosnawintang, Rosnawintang; Nusantara, Ambo Wonua; Muthalib, Abd Aziz (International Journal of Economics and Financial Issues, 2017)
This study aims to investigate the effect of Rupiah/US dollar exchange rate on the volume of Indonesia's export. It analyzes monthly data spanning from January 2001 to November 2015. An econometric model used to analyze the data is the difference equation model. Result of analysis found that in the long term the exchange rate of rupiah/US dollar affects export. This long-term influence is negative, in that each 1% increase (decrease) in rupiah/US dollar is always followed by 0.24% fall (rise) in export. Furthermore, in the short term there is an effect of the exchange rate of rupiah/US dollar on export and the effect is also negative. Indonesian government needs to conduct a policy aimed at increasing industrial outputs that can boost exports. The government also needs to implement a monetary policy to ensure that the exchange rate of rupiah remains stable. Keywords: Exchange rate, export, difference equation model JEL Classifications: F140, F310, G150